Pierre Teilhard de Chardin (1881-1955), Geologist and Palaeontologist. Historical recovery of his scientific work - Sequeiros, Leandro (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The year 2005 marks half a century since the death of the Jesuit Pierre Teilhard de Chardin (1881-1955). After his death, his philosophical and theological works could be published, were translated to others languages and disseminated throughout the world -one of the most prominent publishing phenomena of the XXth century. Teilhard focused on cosmic evolution through time, attempting, from the data provided by the earth sciences and life sciences, to construct a synthesis among science, philosophy, theology and mysticism. When the compilation of Teilhard’s strictly geological and paleontological works was published (due to the efforts of Drs. N. and K. Schmitz-Moortmann) in 11 volumes entitled Oeuvre Scientifique in Switzerland in 1971, the enthusiasm for Teilhard’s thought had already passed. Therefore the dissemination of this collection hardly attained the extent that it deserved. This paper aims to recover this lesser-known aspect of Teilhard: that of geologist and paleontologist.